STUDY OF AMMONIA VOLATILIZATION IN SOME NORTHERN IRAQ SOILS - M. Alobaidi; R. Al-Hamdany; M. Saaid (Mesopotamia Journal of Agriculture)
Ammonia volatilization phenomena from urea fertilizer was studied by using three different textures of calcareous soil(loamy sand ,clay loamand clay) from Mosul city – northern Iraq, classified as calciorthids .Urea was added at three rates (100,200 and 400 mg N.kg-1),using plastic pots (5kg soil) during Spring season 2008 with average minmum and maximum temperature (8-22cْ ). The soil moisture content was monorated around field capacity during period of incubation.The amount of ammonia volatilized from surface was measured after 5,12,27,39,,,and 53 days.The results showed that a higher accumulationof NH3 volatilization was in loamy sand soil followed by clay loam ,then clay soil.The results also showed a significant increases in the accumulated NH3volatilized with increasing fertilizer rates and incubation periods.The mathematical discrption of kinetics equation showed the following order: parabolic diffusion , first order , power function ,second order ,elovich ,and zero order equations respectively according to a highest R2 and lowest SE values. The rate coefficients of parabolic diffusion equation were high at loamy sand when compered with the other textures. Also the increasing rate of urea fertilization from 100 to 400 mg N.kg-1soil caused an increase in the rate of coefficient of NH3 volatilization from (0.118 -0.392) ,(0.108 -0.145) and (0.04-0.108) mg.kg-1 day-1/2 for loamy sand ,clay loam ,and clay soils respectivily.Using a hetrogenous diffusion model showed the sutability of this model to describe the volatilization potential under fertilization non-stability.